Revisão bibliográfica: erros causados por raios cósmicos em dispositivos eletrônicos - Paulo, Isabella Moreira de Sousa (Universidade Federal de São Carlos, 2023)
Cosmic rays, coming from outer space, can penetrate eletronic devices in order to change several characteristics such as functioning, performance and useful life. These particles are composed of an atomic nuclei, made up of ultra energetic protons and neutrons, that travel at high speeds towards the earth's surface, due to their high energy they can easily penetrate electrical and electronic components. These effects are easily found at higher altitudes, but can be observed at sea level on a smaller scale. With the advancement of microelectronics, the collision of these particles with electronic components generates a parasitic electrical charge that harms the operation of several devices, from memories, power electronics to relays and supercomputers. Thus, the purpose of this work is to report and provide an in-depth understanding of the influence of cosmic rays on the operation of electrical and electronic components, through a review of data available in the literature. The aim is to assess the impact on the operation of electronic components, electrical devices, and the advancement of new technologies.
Literature review: errors caused by cosmic rays in electronic devices
Keywords: Circuitos eletrônicos; Dispositivos elétricos; Raios cósmicos; ENGENHARIAS::ENGENHARIA ELETRICA::CIRCUITOS ELETRICOS, MAGNETICOS E ELETRONICOS